Modelo de Ising: um estudo sobre os algorítimos Metropolis e Wang-Landau - Santos, Abel Nascimento Ribeiro (2017)
In this work we present a study of the thermodynamical properties of the spin-1=2 two-dimensional Ising model with ferromagnetic interactions at zero external magnetic eld. We used Monte Carlo simulations, through Metropolis andWang-Landau algorithms. The critical exponents and the corresponding critical temperatures are obtained by both methods using the nite-size scaling hypothesis. A comparison between the exact values and the results obtained from both algorithms was made, not only quantitatively but also in terms of computational times.